The role of dysbiosis in shaping host immunity in endometrial cancer development - Wierzbińska, Wiktoria; Kuźmycz, Olga; Kowalczyk, Aleksandra; Stączek, Paweł (Frontiers in Immunology, 2025)
In recent years, research into the background of carcinogenic processes has increasingly focused on the role of the tumor microenvironment (TME) in tumorigenesis. In addition to the presence of tumor cells and non-malignant components, which include immune cells, extracellular matrix elements, stroma, and endothelial cells, the microbiome is now increasingly being classified as an integral part of the TME. The establishment of the Human Microbiome Project (HMP) in 2007 along with the development of next-generation sequencing (NGS) techniques proved to be a breakthrough in terms of human microbiota research, shedding new light on the existing knowledge of microorganisms inhabiting various niches of the human body and their functions. Emerging scientific evidence from preclinical and clinical studies indicates significant differences in the microbiome composition between tumor tissues and benign controls. The presence of specific pathogenic strains within a tissue may play a key role in the initiation and progression of inflammation, which not only may be directly responsible for the stimulation of tumorigenic processes but may also affect the destabilization of the host genome, causing significant disruption of its metabolism. The role of microorganisms in the induction and promotion of pathological processes, including cancer, has been confirmed in many studies to date. Recent years of research on the microbiota of the female reproductive tract (FRT) have not only indicated that the endometrium has its unique microbial composition but have also made it possible to point out differences in composition between the microbiome of healthy and tumor-lesioned tissue, suggesting a potential role for dysbiotic disorders in the pathogenesis of endometrial cancer (EC). In this review, we aim to highlight the complex interplay between bacterial interactions and host immunity, and how this phenomenon contributes to the development and progression of endometrial cancer.